On the Variation of the Effect of Natural Gas Fraction on Dual-Fuel Combustion of Diesel Engine Under Low-to-High Load Conditions - Yousefi, Amin; Birouk, Madjid; Guo, Hongsheng (Frontiers in Mechanical Engineering, 2020)
Natural gas-diesel dual fuel (NDDF) engine has the potential to significantly reduce carbon dioxide (CO2) and particulate matter (PM) emissions, while retaining diesel engine’s high efficiency and reliability. The operation and performance of NDDF engine depend on natural gas energy fraction (%NG), which ranges from low %NG, where diesel fuel provides most of the combustion energy, to high %NG where diesel fuel is used only to initiate combustion. Although pertaining published studies demonstrated that the effect of %NG on the combustion performance and emissions of NDDF engine depend upon the engine load, none of these studies discussed the reasons behind this dependence. The present study attempts to shed light on this issue by experimentally and numerically investigating the effect of different %NGs on NDDF engine under different load conditions. Both experimental and numerical results revealed that the peak pressure rise rate (PPRR) first increases and then drops with increasing %NG under all load conditions. The calculated local equivalence ratio and charge temperature contours showed that increasing %NG to a certain limit increases local equivalence ratio inside the ignition kernel which implies that more premixed natural gas – air mixture participates in reactions during the premixed combustion stage. This results in an increased flame temperature and higher PPRR right after ignition. However, increasing %NG beyond this range decreases local equivalence ratio inside the ignition kernel which leads to lower PPRR. Increasing %NG retards the combustion phasing at low to medium load conditions. However, increasing %NG generally advances the combustion phasing under medium to high load conditions due to the fact that the flame propagation speed of natural gas – air mixture increases with %NG at medium to high load conditions. Methane emissions grow with increasing %NG under all examined engine load conditions. However, this growth becomes much smaller under medium to high engine load conditions. Increasing %NG significantly increases GHG emissions under lower load conditions. However, using advanced diesel injection timing decreases GHG emissions of NDDF engine under lower load conditions. Increasing %NG decreases GHG emissions by 6 to 11% under medium to high load conditions.